Singing Yoruba Christianity : music, media, and morality - Brennan, Vicki L. (African expressive cultures., 2018)
Singing the same song is a central part of the worship practice for members of the Cherubim and Seraphim Christian Church in Lagos, Nigeria. Vicki L. Brennan reveals that by singing together, church members create one spiritual mind and become unified around a shared set of values. She follows parishioners as they attend choir rehearsals, use musical media'hymn books and cassette tapes'and perform the music and rituals that connect them through religious experience. Brennan asserts that church members believe that singing together makes them part of a larger imagined social collective, one that allows them to achieve health, joy, happiness, wealth, and success in an ethical way. Brennan discovers how this particular Yoruba church articulates and embodies the moral attitudes necessary to be a good Christian in Nigeria today.